Mandela’s Favourite African Folktales (Altre Modernità, 2014)
In this essay I would like to examine the selection of African tales that Nelson Mandela took care to leave as heritage to the future generations, not only to children, and not only to African children. The fact that a political leader, ex freedom fighter and political prisoner dedicated his time to the collection and editing of stories from all over the African continent to be addressed to new readers as simple entertainment or as educational tools clearly testifies to the great humanity, culture, and open mindedness of one of the most important men of our times. In his most recent autobiographical writing Conversations With Myself, Mandela claimed his double affiliation to both his own indigenous culture as well as to western culture. Moreover, he recalled with affection a dear pastime of his childhood:After supper we would listen enthralled to my mother and sometimes my aunt telling us stories, legends, myths and fables which have come down from countless generations, and all of which tended to stimulate the imagination and contained some valuable moral lesson. (p. 10)Thus, it is not surprising that such a charismatic public figure, as Mandela has been, was also interested in- and worried about- the future survival of a cluster of traditional folktales with their lively, specific and “valuable moral lesson”. It is my intention to verify if there might be a dialogue between the western tradition of folktales where animals are protagonists and speak as anthropomorphic figures and the facets of the African traditions and cultures from which Mandela draws inspiration. Among the critical tools on this topic, Tess Cosslett’s Talking Animals in British Children’s Fiction (2006) seems to provide a useful starting point, together with the latest studies in the volume Dall’ABC a Harry Potter (2011), among others. Moreover, aspects of “orature” will be discussed with reference to the stories chosen by Nelson Mandela. Finally, an attempt will be made to connect these types of animal tales to works of figurative art, particularly paintings, by African artists, which might share the same moral message and which might trigger similar narratives.